(untitled) (Proceedings of the International Conference on Public Health, 2017)
The major issue of Tuberculosis (TB) control program in Indonesia including Bali is the low cases detection rate (32%). An intensive presumptive TB finding through screening program and then followed by diagnosis procedure is important to conduct. Meanwhile, perceived stigma is a social determinant of health that strongly associated to health-seeking behaviour. This study aimed to assess the association of perceived stigma towards TB to diagnosis procedure implementation among presumptive TB casesscreened from diabetes mellitus (DM) patients. This was an operational research during the TB screening program among DM patients. The samples were collected consecutively from January until March 2016 at 11 public health centres (PHC) in Denpasar City, Bali Province. Data were collected via interview using structured questionnaire. Logistic regression was used for statistical testing. During 3 months implementation of screening program, there were 567 DM patients screened, 342 of them were presumptive TB cases and were recommended to follow TB diagnosis procedures. There were only 87(25,4%) who followed the procedure and 255 (74,6%) refused to participate. The refusal to diagnosis procedure was associated to the TB stigma (OR=1.7; 95%CI: 1.03-2.9). Meanwhile, perceivedstigma towards TB wasassociated to the lack knowledge of TB (OR=2.0; 95%CI: 1.3-3.2) and the lack of family support (OR=1.8; 95%CI: 1.1-2.7). The diagnosis procedure coverage among presumptive TB cases screened from DM patient was still low. The perceived stigma towards TB is contributed to the high proportion of presumptive TB cases who did not follow thediagnosis procedure. Therefore, a comprehensive education toincrease public awareness and supportto the TB program are necessary.